Answer :

LHS


= {1 + cotx – (-cosecx)} {1 + cotx + (-cosecx)}


= {1 + cotx + cosecx} {1 + cotx – cosecx}


= {(1 + cotx) + (cosecx)} {(1 + cotx) – (cosecx)}


We know that (a + b) (a – b) = a2 – b2


= (1 + cotx)2 – (cosecx)2


= 1 + cot2x + 2 cotx – cosec2x


We know that 1 + cot2x = cosec2x


= cosec2x + 2 cotx – cosec2x


= 2 cotx


= RHS


Hence proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Prove that :
<
RD Sharma - Mathematics

prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Find the values oRD Sharma - Mathematics

Find the values oRD Sharma - Mathematics

Find the values oRD Sharma - Mathematics

Find the values oRD Sharma - Mathematics

prove that :
<
RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

Find the values oRD Sharma - Mathematics